Epilepsi dan Budaya - Nurwinta Catur Wulan Maryanti (Faculty of Psychology Universitas Gadjah Mada, 2016)
This paper shows an analysis on several literature reviews. The aim of this article is to understand epilepsy in multiple cultures. Epilepsy is considered different across countries and cultures. It is a neurological disorder, characterized by spontaneous and periodic seizures. It is not a new illness. In ancient times, epilepsy has been known as a form of religious experience associated with satanic or sacred diseases, spirits' attacks, 'possessions,' and in some cultures identical to madness. Epilepsy has detrimental effects on patient psychologically, economically, socially and culturally. These effects include social isolation, stigmatization, or disability that can lead to poor learning outcomes and job opportunities. Negative social stigma, negative attitudes, misunderstandings, discrimination, and misperceptions experienced by epileptic patients around the world, causes them to feel trapped in the dark and socially withdrawn.